A Schiff base of 2-((E)-(2-amino-5-methylphenylimino)methyl)- 5-(difluoromethoxy)phenol and its applications on fluorescent chemosensor for selection of Mg2+ ion, molecular docking, and anticancer activity - Iyappan Mathivanan, Dhineshkumar Ezhumalai, Anbuselvan Chinnadurai (Journal of Applied Pharmaceutical Science, 2020)
A novel Schiff base of 2-((E)-(2-amino-5-methylphenylimino)methyl)-5-(difluoromethoxy)phenol (R) was synthesized and characterized by FTIR, 1H&13C-NMR, and mass spectrometry. The receptor turned yellow and then green in the presence of Mg2+ molecules, with the intervention of different metal ions. The selectivity and sensitivity of Mg2+ ion caused the maximum fluorescence emission intensity at 524 nm, with an excitation wavelength at 378 nm. Further experiments confirmed that receptor R binds with Mg2+. Job’s plot conforms to a 1:1 stoichiometry complex formation. The strong fluorescence is owing to the photoinduced electron/energy transfer effect. The receptor was recovered by an ethylenediaminetetraacetic acid titration and the emission intensity also returned to a value equivalent to the unbound ligand. protein data bank: 4J96 was used for the molecular docking of receptor R. The cytotoxicity effect treatment was carried out by increasing the concentration of HeLa cells to predict IC50 value. The highest occupied molecular orbital/lowest unoccupied molecular orbita energy gap calculated and compared between R results as 3.48 eV and R-Mg2+ alpha and the beta value calculated a low energy value at 2.27 eV.
Keywords: Schiff base, Mg2+ ion, colorimetric, Fluorometric, cytotoxicity, DFT.